Case report: Clinical course and treatment of SARS-CoV-2 in a pediatric CAR-T cell recipient with persistent hypogammaglobulinemia - Sanders, Howard; Callas, Christina; St. Amant, Helaine; Chung, Jong; Dimitriades, Victoria R.; Nakra, Natasha A. (Frontiers in Pediatrics, 2023)
This report describes a pediatric patient who underwent chimeric antigen receptor (CAR) T-cell therapy for refractory B-cell acute lymphoblastic leukemia (B-ALL) four years prior, with resultant hypogammaglobulinemia for which he was receiving weekly subcutaneous immune globulin. He presented with persistent fever, dry cough, and a tingling sensation in his toes following a confirmed COVID-19 infection 3 weeks prior to admission to the hospital. His initial nasopharyngeal SARS-CoV-2 PCR was negative, leading to an extensive workup for other infections. He was ultimately diagnosed with persistent lower respiratory tract COVID-19 infection based on positive SARS-CoV-2 PCR from bronchoalveolar lavage (BAL) sampling. He was treated with a combination of remdesivir (antiviral) and casirivimab/imdevimab (combination monoclonal antibodies) with immediate improvement in fever, respiratory symptoms, and neurologic symptoms.